The U.S. - China Power Rivalries in the Obama Era: The Limits of American Alliance and the Challenges of (Not) Choosing Sides in Southeast Asia - Suporn, Thapiporn (Thai Journal of East Asian Studies, 2019)
This article aims to explain the limits of the American military alliance in Southeast Asia during Barack Obama’s administration, in the context of China’s rise. Preoccupied by the mainstream narrative asserting that great power rivalries between the U.S. and China would inevitably force Southeast Asian states to choose sides, this article, however, strongly disagree with such narrative. Rather, it is more likely that even though the Obama administration would attempt to form an alliance network to counterbalance and deter China’s influence, the Washington containment coalition was unlikely to gain many supporters in Southeast Asia due mainly to different interests and needs among Southeast Asian states. Moreover, even some states have faced China’s aggressive behavior in the case of the South China Sea disputes, these states have realized that they should maintain its economic and security relations with both China and the U.S. instead of choosing sides, which are considered as a risky business.